2019
DOI: 10.1002/jcla.23068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum Lp‐PLA2 levels in ischemic stroke patients with H‐type hypertension or non‐H‐type hypertension

Abstract: Background Increased serum Lp‐PLA2 levels have been reported in patients who experienced an ischemic stroke; however, the relationship between Lp‐PLA2 and H‐type hypertension in patients with ischemic stroke remains unclear. Methods In the present study, we investigated the correlation between serum Lp‐PLA2 and H‐type hypertension in patients with ischemic stroke. A total of 135 patients who experienced acute ischemic stroke were enrolled in Tianjin Huanhu Hospital during October 2015 to May 2016. The demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As a high-risk factor for atherosclerotic vascular disease and cardiovascular disease, Lp-PLA2 has received more and more attention. Recent studies have found that the level of Lp-PLA2 is not only related to the formation of lipid atherosclerotic plaques, ischemic stroke and vascular inflammation, but also to the occurrence of coronary heart disease (Bonnefont-Rousselot, 2016;Qiao et al, 2020;Qin et al, 2020). Lipid metabolism plays an important regulatory role in the occurrence and development of cardiovascular and cerebrovascular diseases (Esenwa and Elkind, 2016;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a high-risk factor for atherosclerotic vascular disease and cardiovascular disease, Lp-PLA2 has received more and more attention. Recent studies have found that the level of Lp-PLA2 is not only related to the formation of lipid atherosclerotic plaques, ischemic stroke and vascular inflammation, but also to the occurrence of coronary heart disease (Bonnefont-Rousselot, 2016;Qiao et al, 2020;Qin et al, 2020). Lipid metabolism plays an important regulatory role in the occurrence and development of cardiovascular and cerebrovascular diseases (Esenwa and Elkind, 2016;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By activating cytokines and adhesion factors, vascular endothelial cells become dysfunctional, thereby increasing blood pressure. ③ Lp-PLA2 promotes the release of inflammatory mediators, collagen deposition and fibroblast proliferation in inflammatory reaction sites, and platelet aggregation, which plays an anti-inflammatory and anti-atherosclerosis role and promotes the progress of HDP (16)(17)(18). As a marker of inflammatory reaction in the body, CRP can activate platelet activity, inhibit platelet activating factor, promote platelet release of arachidonic acid and platelet aggregation, and inhibit the binding of platelet activating factor and neutrophils, which plays a role in regulating inflammatory reaction (19).…”
Section: Discussionmentioning
confidence: 99%
“…Increased circulating LP-PLA2 levels can help predict increased risks of MI, stroke, and cardiovascular death. 26 Elevated serum Lp-PLA2 levels have been reported in patients with ischemic stroke, 27 , 28 and is an independent risk factor for AIS. 29 , 30 The Lp-PLA2 G994T gene polymorphism may be an independent risk factor for ischemic stroke in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%